DNA Barcoding of Ornamental Crab Geosesarma in South-Slope Mount Slamet Central Java, Indonesia - Winarni, Elly Tuti; Rofiqoh, Aswi Andriasari; Bhagawati, Dian; Pulungsari, Anastasia Endang; Mahmoud, Hanan Hassan Alsheikh; Nuryanto, Agus (Universitas Negeri Semarang, 2024)
Geosesarma shows intraspecific carapace color variation, which might lead to species misidentification. The problem can be solved using DNA barcoding. There is one research about Geoserarma from the southern slopes of Mount Slamet, but samples were only collected from the Banjaran River for morphological identification. Here, we collected samples from wider areas covering south slope and applied molecular identification. This research aims to assess Geosesarma diversity in south-slope Mount Slamet Central Java, Indonesia based on the cytochrome c oxidase 1 gene barcoding. Surveys were carried out at six sites. Taxonomic identification was done using the barcoding technique. Four morphotypes were obtained during the research. Three morphotypes with the square carapace were identified as Geosesarma, while the remaining one morphotype was included in Parathelphusa. The three Geosesarma morphotypes were barcoded as Geosersarma dennerle because their genetic identity was more than 97% of the G. dennerle sequence in Boldsystems. In contrast, the Parathelphusa morphotype was barcoded as P. convexa with a genetic identity of 97.50%. It can be concluded that the Geosesarma crab on the south-slope Mount Slamet only consists of one species but has carapace and claw color variations. The data are essential for Geosesarma market development and conservation in the region.